Towards Versatile Simulation Models of Transport Nodes - Norbert Adamko; Valent Klima; Antonin Kavicka (Communications - Scientific letters of the University of Zilina, 2005)
The paper deals with analysis of characteristics of simulation tools and models which are required for support of dispatcher’s decisions in real operation, training of dispatchers and education. Further, a concept of simulation tool is discussed that will allow the construction and development of simulation models in which support for re/design of railway system, its management and also the training of dispatchers will be integrated.